Development of Cold Hardy, Large Patch Resistant Zoysiagrass Cultivars for the Transition Zone - Mingying Xiang; J. Fry; M. Kennelly (Kansas Agricultural Experiment Station Research Reports, 2016)
TAES 5645, aZ. japonicagenotype that exhibited resistance to large patch in preliminary studies, was used as a breeding parent and crossed with 22 cold hardy zoysiagrasses, resulting in 985 progeny. These progeny were evaluated for cold hardiness and agronomic traits (establishment rate, overall quality, spring greenup, leaf texture, and genetic color) in Manhattan, KS; West Lafayette, IN; and Dallas, TX; from 2012 to 2014. From this work, 60 progeny were identified for further evaluation in larger plots. During the 2015-2016 establishment year, experimental line 6102-47 showed good vigor and spring green up rate, which is comparable to ‘Meyer,’ the standard cultivar in our area.
Keywords: Turfgrass; zoysia; large patch